1993
DOI: 10.1177/095632029300400202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Topoisomerase Inhibitors as Potential Antiviral Agents

Abstract: SummaryAnti-eukaryotic topoisomerase drugs, Camptothecin and Etoposide, were tested for their ability of selectively interfering with the replication of simian virus 40 (SV40) DNA. Nalidixic acid was also assayed for a comparison, since the compound has been previously reported to affect papoyijvirus growth. Our results indicate that anti-eukary6tic topoisomerase drugs significantly inhibit viral DNA replication but at . concentrations that are also toxic for uninfected cells. Etoposide treatment produced a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several reports showed antiviral activities of DNA topoisomerase inhibitors. The anti-eukaryotic topoisomerase drugs camptothecin and etoposide were reported to interfere with the replication of simian virus 40 (Maschera et al, 1993). Podophyllotoxin derivatives such as etoposide (VP-16) and teniposide (VM-26) are known to be potent inhibitors of DNA topoisomerase II.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed antiviral activities of DNA topoisomerase inhibitors. The anti-eukaryotic topoisomerase drugs camptothecin and etoposide were reported to interfere with the replication of simian virus 40 (Maschera et al, 1993). Podophyllotoxin derivatives such as etoposide (VP-16) and teniposide (VM-26) are known to be potent inhibitors of DNA topoisomerase II.…”
Section: Discussionmentioning
confidence: 99%
“…However, their use as anti-virals is far scarcer. Some studies have been performed in order to assess their potential as inhibitors of infection by several types of viruses, such as simian virus 40 [ 103 ], Kaposi’s sarcoma-associated herpesvirus [ 104 ] and HIV [ 105 ]. However, most of these studies have found that the drugs tested are either ineffective in inhibiting viral replication, or that they do so while simultaneously causing high cytotoxicity, thereby hindering their clinical use.…”
Section: Controlling Asf Through Inhibition Of the Viral Type II Tmentioning
confidence: 99%
“…1 also inhibits replication of this virus, and deletion of Top1 is able to rescue virus infectivity from inhibition by 1 . Camptothecin has similar antiviral effects on simian virus 40, parvoviruses, adenoviruses, herpesviruses, and other DNA viruses; these studies (most from the 1990s) are summarized in the excellent review by Pantazis …”
Section: Uses Beyond Cancermentioning
confidence: 99%
“…1 also inhibits replication of this virus, and deletion of Top1 is able to rescue virus infectivity from inhibition by 1. 388 Camptothecin has similar antiviral effects on simian virus 40, 389 More recently, Takahashi et al 391 found that host Top1 interacts with the RNA-dependent RNA polymerase of Ebola virus (by coimmuoprecipitation) and aids in virus replication, and that Top1 knockdown reduces viral polymerase activity and Ebola replication. Camptothecin's role in preventing HIV infection and transmission has also been documented.…”
Section: Antiviral Activitymentioning
confidence: 99%